40Ar-39Ar analyses of an Antarctic meteorite Yamato-791197 of probable lunar origin - Kaneoka,Ichiro; Takaoka,Nobuo (1986)
P(論文) ^<40>Ar-^<39>Ar analyses have been applied to an Antarctic meteorite Yamato-791197 (Y-791197), an anorthositic regolith breccia of probable lunar origin (YANAI and KOJIMA, Mem. Natl Inst. Polar Res., Spec. Issue, 35,18,1984). The clast sample (Y-791197,96) shows a plateau ^<40>Ar-^<39>Ar age of 4065±93 Ma at higher temperatures, which corresponds to typical age groups obtained for lunar rocks of highland origin. The matrix sample (Y-791197,97) contains a large amount of trapped Ar (^<40>Ar : ∿9×(10)^<-4>(cm)^3STP/g) with the ^<40>Ar/^<36>Ar ratio of about 2.5 at higher temperatures, which implies that the trapped Ar is mostly of solar wind origin. This makes it difficult to estimate a reasonable ^<40>Ar-^<39>Ar age for this portion. The present result supports a presumption that Y-791197 originated from the moon's surface as a lunar highland breccia. departmental bulletin paper